Unraveling the regulatory role of endoplasmic-reticulum-associated degradation in tumor immunity - Qin, Xiaodan (Crit Rev Biochem Mol Biol, 2020)
During malignant transformation and cancer progression, tumor cells face both intrinsic and extrinsic stress, endoplasmic reticulum (ER) stress in particular. To survive and proliferate, tumor cells use multiple stress response pathways to mitigate ER stress, promoting disease aggression and treatment resistance. Among the stress response pathways is ER-associated degradation (ERAD), which consists of multiple components and steps working together to ensure protein quality and quantity. In addition to its established role in stress responses and tumor cell survival, ERAD has recently been shown to regulate tumor immunity. Here we summarize current knowledge on how ERAD promotes protein degradation, regulates immune cell development and function, participates in antigen presentation, exerts paradoxical roles on tumorigenesis and immunity, and thus impacts current cancer therapy. Collectively, ERAD is a critical protein homeostasis pathway intertwined with cancer development and tumor immunity. Of particular importance is the need to further unveil ERAD’s enigmatic roles in tumor immunity to develop effective targeted and combination therapy for successful treatment of cancer.